Gambaran Pengetahuan dan Sikap Pencegahan Covid 19 Pada Masyarakat RW 02 RT 05 di Malengkeri Kelurahan Mangasa Kota Makassar - Esse Puji Pawenrusi; Muhammad Hatta; Kasmira (Jurnal Mitrasehat, 2021)
The World Health Organization (WHO) states that COVID-19 has become a worldwide pandemic disease (Andrews, et al., 2020). Ministry of Health COVID-19 Republic of Indonesia, showed that as of November 2020, the total number of COVID-19 positive patients in the world reached 58,900,547 people, with 1,393,305 deaths. In Indonesia, the total COVID-19 positive patients amounted to 511,836 cases, with 429,807 patients cured and 16,225 patients dying. The purpose of this research is to find out the description of knowledge and attitudes of COVID-19 prevention in the community of Malengkeri Mangasa Village, Makassar City. This type of research is descriptive research. The population in this study was the malengkeri community of Mangasa Village, Makassar city as many as 120 families. Sample withdrawal using Purposive Sampling technique with a sample count of 63 family heads. The results of this study showed that most of the malengkeri people in Makassar have COVID-19 knowledge, which is enough as many as 54 people (85.7%), and less than 9 people (14.3%) and positive attitude as many as 62 people 98.4%), negative 1 person as much (1.6%). It concludes that most malengkeri people have sufficient knowledge about COVID-19 prevention and positive attitudes. Advice for malengkeri people to date more about the development of COVID-19.